Around training pro-health behaviours of people leading an active lifestyle. Sleep as a natural way of regeneration - Kędzia, Piotr (Contemporary problems of physical and health culture, 2022)
Contemporary challenges of physical activity require people who undergo physical effort also an effective strategy of regenerating psychophysical forces and strengthening movement patterns. A rationally built system of pro-health behaviour around training has both immediate and long-term value. In a broader perspective, it achieves the value of self-education and auto-education in the area of caring for one’s own health, thus creating a personalized variant of health education. There are many, well-known or less studied, proposals for measures and methods to supplement or compensate for systematically applied training stimuli. One of them is sleep as a natural and basic means of regeneration of the body.